DILEMA BAHASA MELAYU SEBAGAI BAHASA PENGANTAR PEMBELAJARAN DI PONDOK PESANTREN PATANI THAILAND SELATAN - Phaosan Jehwae (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2014)
The dilemma of Malay language education at Patani, south Thai is depend on the Thai basic political country. Even though some of Thai government basic politics refers to decrease the role of Malay language at kingdom school or boarding school, in reality Malay language is still exist as compulsory language at boarding school. This article also describes the obligation of the students to learn for languages such as Thai, Malay, English, and Arabic. On school hours, the students usually talk with Thai than Malay. The situation happen because Malay language is margined by Thai government educational system.